Engineering students’ perception of Minitab in learning statistics / Wan Nur Shaziayani ... [et al.] - Wan Mohd Rosly, Wan Nur Shaziayani; Syed Abdullah, Sharifah Sarimah; Ahmad Shukri, Fuziatul Norsyiha; Omar, Mawardi (Unit Penerbitan JSKM, 2025)
The integration of statistical software in engineering education has become essential for bridging the gap between theoretical concepts and practical applications. This study examines the effectiveness of Minitab software in enhancing students' understanding of statistical concepts in the STA408 course at Universiti Teknologi MARA (UiTM) Penang. A survey was conducted among 26 engineering students from various disciplines, assessing their perceptions of Minitab’s usability, impact on learning outcomes, and relevance to future careers. Descriptive statistical analysis revealed that students generally had a positive experience with Minitab, particularly appreciating its visualisation features for interpreting statistical outputs. The findings suggest that incorporating Minitab into statistics courses promotes active learning, improves problem-solving skills, and enhances confidence in statistical analysis. As industries increasingly rely on data-driven decision-making, equipping engineering students with proficiency in statistical tools like Minitab is crucial for their academic and professional development.